Perceived knowledge of midwives regarding differences in cultural practices of pregnant women at a Regional Hospital in Gauteng - Ngunyulu, Roinah Nkhensani (University of Pretoria, 2022)
Dissertation (MSc (Nursing))--University of Pretoria, 2022.